2014
DOI: 10.14336/ad.2014.0209
|View full text |Cite
|
Sign up to set email alerts
|

The Intricate Interplay between Mechanisms Underlying Aging and Cancer

Abstract: Age is the major risk factor in the incidence of cancer, a hyperplastic disease associated with aging. Here, we discuss the complex interplay between mechanisms underlying aging and cancer as a reciprocal relationship. This relationship progresses with organismal age, follows the history of cell proliferation and senescence, is driven by common or antagonistic causes underlying aging and cancer in an age-dependent fashion, and is maintained via age-related convergent and divergent mechanisms. We summarize our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 298 publications
(309 reference statements)
0
21
0
Order By: Relevance
“…In our study, only 7% of all participants believed chemical or occupational exposure might have caused their disease, and a mere 8% of occupationally exposed participants mentioned this as a cause, even though certain types of occupational exposure are established risk factors. Surprisingly, none of our participants mentioned ageing even though this is an established risk factor for cancer in general [20,21]. An explanation may be that only patients younger than 75 were recruited.…”
Section: Stratificationmentioning
confidence: 75%
“…In our study, only 7% of all participants believed chemical or occupational exposure might have caused their disease, and a mere 8% of occupationally exposed participants mentioned this as a cause, even though certain types of occupational exposure are established risk factors. Surprisingly, none of our participants mentioned ageing even though this is an established risk factor for cancer in general [20,21]. An explanation may be that only patients younger than 75 were recruited.…”
Section: Stratificationmentioning
confidence: 75%
“…Among such diseases are arthritis, diabetes, heart disease, kidney disease, liver dysfunction, sarcopenia, stroke, neurodegenerative diseases (including Parkinson's, Alzheimer's and Huntington's diseases), and many forms of cancer [3, 6, 9, 12, 1518, 21, 79, 94105]. Because the major aspects of aging and age-related pathology are conserved across phyla [1, 46, 1013, 16–18], it is noteworthy that this study, recent findings [78] and our ongoing research have revealed several features of the six PEs as potential interventions for decelerating chronic diseases of old age.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have shown that knockdown of RBP4 significantly reduces ovarian cancer cell migration and proliferation driven through the RhoA/Rock1 and extracellular signal-regulated kinase (ERK) pathways [26].The aim of our studies was to explain the role of RBP4 protein in the growth and metastatic spread of two murine breast cancer isogenic cell lines (derived from a single tumor of BALB/c mouse); metastatic 4T1 and nonmetastatic 67NR, representing basal-like and luminal-like phenotype, respectively [2,4]. Moreover, because, in many cases, cancer is associated with the aging process (largely reviewed in [27]) and aging affects the metastatic phenotype of cancer cells as well as tumor angiogenesis [28][29][30], we decided to include in our studies young and aged animals. To the best of our knowledge, no previous studies have investigated the effect of RBP4 protein on the metastatic spread of cancer.…”
mentioning
confidence: 99%